Prefrontal Cortex Oxygenation Evoked by Convergence Load Under Conflicting Stimulus-to-Accommodation and Stimulus-to-Vergence Eye-Movements Measured by NIRS - Hans O. Richter; M. Forsman; G. H. Elcadi; R. Brautaset; John E. Marsh; John E. Marsh; C. Zetterberg; C. Zetterberg (Frontiers in Human Neuroscience, 2018)
Purpose: To extend our knowledge of the functional linkages between visual fatigue and regional cerebral prefrontal cortex (PFC) oxygenation, we measured time related hemodynamic changes over the right dorsolateral prefrontal cortex (dlPFC) during convergence load under conflicting stimulus-to-accommodation and stimulus-to-vergence eye movements with and without concurrent mental load.Methods: Twenty healthy participants with a median age of 28 years (range: 18–44 years) fixated upon a vertical bar presented separately to the left and right eyes, using polarized filters, during four counterbalanced 10-min periods: (i) no accommodation/vergence conflict (Control, Ctrl); (ii) added convergence load and accommodation/vergence conflict (Conv); (iii) added cognitive load only (Cog) and; (iv) a combination of added cognitive and convergence load and accommodation/vergence conflict (Cc). Viewing distance was 65 cm. Non-invasive measurements of hemodynamic activity over the dlPFC were quantified by functional near-infrared spectroscopy (fNIRS). During the two-convergence load conditions, the horizontal disparity of the two bars varied dynamically from no disparity to a disparity set 20% below the individual threshold for diplopia. Cognitive load was induced by the n-back-2 test which required the subject to memorize and recall the changing colors of the horizontal bars and decide when a given color was the same as that occurring two colors previously. fNIRS data were averaged over 10-s windows centered at 0, 2, 4, 6, 8, and 10 min of each task, subtracted from a 20-s baseline window immediately preceding the visual task, and then represented as changes in oxygenated hemoglobin (ΔHbO2), deoxygenated hemoglobin (ΔHHb) and total hemoglobin (ΔtHb).Results: Linear mixed model analyses showed that hemodynamic activity was systematically influenced by time (p < 0.001). The group-averaged time-related level of change across the viewing conditions did not differ when compared with one another (p > 0.05). Larger convergence eye-movement responses under conflicting stimulus-to-accommodation, and stimulus-to-vergence over time, increased ΔHbO2 and ΔtHb only in condition Cc and after 8 min of task time (p < 0.10 for min-6 and min-8: p < 0.05 for min-10).Discussion: Collectively, our data suggest that HbO2, HHb, and tHb, recorded over the dlPFC with fNIRS, can be used to assay the degree to which supervisory oculomotor control processes are activated during visually deficient near work.